Optimization of Preparation Conditions for Melamine Urea Formaldehyde Based Adhesive for Plywood Application using Response Surface Methodology - Ong, Huei Ruey; Reddy Prasad, D. M.; Khan, Maksudur R. (2016)
Filler is added to adhesive formulations to reduce resin utilization leading to cost savings. Melamine urea formaldehyde (MUF) resin has been synthesized in the laboratory. The palm kernel meal (PKM) and palm shell (PS) are used as fillers to formulate the melamine urea formaldehyde (MUF) resin based adhesive for interior plywood manufacturing. These formulations are compared with commercialized industry wheat flour (IF) filler. Response surface methodology (RSM) is used for identification of the optimum temperature and pressing time for wood adhesive performance. The experiments have been conducted in the temperature range from 100 to 150°C and pressing time from 50 s to 250 s. The result indicates that the effect of the filler type on plywood shear strength and formaldehyde emission is significant. The optimum shear strength and formaldehyde emission performance of PKM, IF and PS are 1.41 MPa, 1.30 MPa, 1.21 MPa and 0.9988 mg/L, 0.5345 mg/L, 1.2735 mg/L respectively. In addition, the optimum hot press temperature and time of PKM, IF and PS are 124.9°C, 130.9°C, 127.9 °C and 156 s, 153 s, 149 s respectively. This work concludes that, PKM based MUF adhesive resins exhibit potential applications involved in plywood production.